If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 895 + 30g Multiply f * x fx = 895 + 30g Solving fx = 895 + 30g Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 895x-1 + 30gx-1 Simplifying f = 895x-1 + 30gx-1 Reorder the terms: f = 30gx-1 + 895x-1
| 15n^2+17n=4 | | -2=-20+y | | -5b+4=39 | | 12+m=-8 | | B/3+6=24 | | -3n+4=19 | | 19=-8+n | | 6+5f+11r-7+3f+5(x+3)= | | -6(3x+9)+7= | | 25p+6p^2=-4 | | x^4+4x^3+(-8x^2)+2=0 | | x^2-4x+13=29 | | -3-5x=-18 | | x^4+4x^3(-8x^2)+2=0 | | .5(4x+13)+.5= | | Log(3)(x+1)-log(3)x=2 | | t+9=-5 | | 32r^2-50=0 | | 7/x+5-1/x-3=5/3 | | -2-a=-2 | | r+6=6 | | x^4+4x^3-8x^2+2=0 | | .5(2x+4)+9= | | 1/2t^2-16=0 | | -80=-8x | | j-92=-20 | | 6x+3+2x-9x+10x=6+7+4x-9 | | 64b^2=4 | | 4y^2+52y+169=0 | | -2-n=-5 | | 1.50/8 | | d-47=42 |